The Negotiation of Identities in Multilingual Settings as Depicted in Indonesia dalem Api dan Bara - Andita Eka Wahyuni; Nurenzia Yannuar; Yazid Basthomi; Suharyadi Suharyadi (Linguistik Indonesia, 2023)
The present study focuses on the negotiation of identities of Kwee Thiam Tjing, the author of Indonesia dalem Api dan Bara ‘Indonesia on Fire and Charcoals’. Our study aims to investigate ways in which he responds to others’ positioning and repositions himself to fit in a particular circumstance under certain dominant power. The results show five domains of identities that may be subject to negotiation: linguistic, ethnic, cultural, role, and social identities. We argue that in colonial Indonesia some identities are negotiable while others are forcefully imposed. Kwee’s translingual practice performed both in writing and in daily life has acquired him a space to fully express his non-negotiable identities. Our study shows how his translingual practice serves as a mediational tool to better negotiate identities, especially in a multilingual environment.